1998
DOI: 10.1093/emboj/17.13.3576
|View full text |Cite
|
Sign up to set email alerts
|

Bax-mediated cell death by the Gax homeoprotein requires mitogen activation but is independent of cell cycle activity

Abstract: Tissues with the highest rates of proliferation typically exhibit the highest frequencies of apoptosis, but the mechanisms that coordinate these processes are largely unknown. The homeodomain protein Gax is downregulated when quiescent cells are stimulated to proliferate, and constitutive Gax expression inhibits cell proliferation in a p21 WAF/CIP -dependent manner. To understand how mitogen-induced proliferation influences the apoptotic process, we investigated the effects of deregulated Gax expression on cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…Here, we have shown that Gax exhibits dual actions in VSMCs of balloon-injured rat carotid arteries, promoting both cell cycle arrest and apoptosis, consistent with previous in vitro observations. 19,20 It is noteworthy that Gax is unable to induce apoptosis in quiescent VSMCs, apoptosis is observed only in proliferating cells, 20 the subpopulation that forms the stenotic lesion in injured vessels. 29 Such a lack of toxicity to quiescent VSMCs indicates that Ad-Gax should prove an advantageous therapeutic strategy for treating conditions characterized by VSMC hyperproliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we have shown that Gax exhibits dual actions in VSMCs of balloon-injured rat carotid arteries, promoting both cell cycle arrest and apoptosis, consistent with previous in vitro observations. 19,20 It is noteworthy that Gax is unable to induce apoptosis in quiescent VSMCs, apoptosis is observed only in proliferating cells, 20 the subpopulation that forms the stenotic lesion in injured vessels. 29 Such a lack of toxicity to quiescent VSMCs indicates that Ad-Gax should prove an advantageous therapeutic strategy for treating conditions characterized by VSMC hyperproliferation.…”
Section: Discussionmentioning
confidence: 99%
“…in a volume of 100 l of either AdGax 19,20 or Ad-ā¤-gal. 19,20,30 The solution was injected via a cannula inserted just proximal to the carotid bifurcation and the vessel was incubated for 20 min, after which the solution was withdrawn and the cannula removed. All transgenes are expressed under control of the cytomegalovirus promoter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For cell cycle analysis and determination of subdiploid DNA content, cultures were harvested by trypsinization, fixed in 70% ethanol overnight, and stained with propidium iodide (Roche, Indianapolis, IN) as previously described (32). A gate was established to count 10,000 events for each sample.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…20 However, homeodomain transcription factors are widely recognized to function as pleiotropic regulators and gax overexpression may also affect VSMC differentiation, migration or viability. 22,61,62 In contrast to the Ad-Gaxtreated arteries, no discernible difference was seen in the extent of neointima formation between the Ad-CMVluctreated and saline-treated arteries in the control group of animals. The ability of Gax overexpression to inhibit neointima formation compares favorably with previous recent results reported by other groups using adenovirusencoded genes for wild-type and mutant form of RB in rat and porcine models, 46,63 the herpes simplex virus thymidine kinase gene in rat, rabbit and porcine models, 26,27,55,56 p21 53 in the rat model and hirudin in the rat model.…”
Section: Enzymes Withmentioning
confidence: 84%